A recombinant two-module form of human properdin is an inhibitor of the complement alternative pathway. (May 2016) - Kouser, Lubna; Abdul-Aziz, Munirah; Tsolaki, Anthony G.; Singhal, Dipti; Schwaeble, Wilhelm J.; Urban, Britta C.; Khan, Haseeb A.; Sim, Robert B.; Kishore, Uday
Highlights: We have expressed thrombospondin repeats 4 and 5 of human in tandem in E. coli as biologically active module. The recombinant module binds to the known ligands of properdin such as C3b, sulfatides and glycosaminoglycans. The recombinant two-module protein inhibits the complement alternative pathway in vitro. Abstract: Properdin upregulates the alternative complement pathway by binding and stabilising the C3 convertase complex (C3bBb). Properdin is a soluble glycoprotein and its flexible rod-like 53 kDa monomers form cyclic polymers (dimers, trimers, tetramers and pentamers). The properdin monomer consists of seven thrombospondin type I repeats (TSR 0–6), which are similar and homologous to domains found in circumsporozoite and thrombospondin-related anonymous proteins of Plasmodium species, ETP100 of Eimeria tenella, various complement components C6-C9, and thrombospondin I and II. Using deletion constructs, TSR4 and TSR5 of human properdin were implicated in C3b binding and stabilising C3 convertase. However, individually expressed TSR4 or TSR5 failed to bind properdin ligands. Here, we have expressed and characterized biologically active TSR4 and TSR5 together (TSR4 + 5) in tandem in Escherichia coli, fused to maltose-binding protein. MBP-TSR4 + 5 bind solid-phase C3b, sulfatides and glycosaminoglycans. In addition, functionally active recombinant TSR4 + 5 modules inhibit the alternative pathway of complement.